Allium Cepa L. Var. Aggregatum Don – A Treasure Of Micronutrients and Non-structural Carbohydrates - Geethanjali, S; Maheshwari, T Uma; Shenbagavalli , S; Geetha, K (Bangladesh Journal of Botany, 2024)
The study was conducted with four aggregatum onion viz., Co (On) 5, Co (On) 6, Local Perambalur (LP) and Local Manachanalur (LM), varieties of Tamil Nadu. Selected micronutrients were analyzed in which, the LP variety was reported to be higher in Na, K, Ca, Zn, Mn, Mg and Se. Similarly, the highest folic acid (48.23 ± 0. 47 mg/Kg) and pyruvic acid (3.02 ± 0. 02µmole g-1) was observed in the same variety. Non-structural carbohydrates, fructose and sucrose were found higher (463.8 ± 0.26 and 257.37 ± 3. 49 mg/kg) in LP variety. However, LM variety is higher in glucose (1169.57 ± 33.73 mg/kg), galactose (234.4 ± 0.62 mg/kg) and maltose (227.2 ± 1.44 mg/kg). This study therefore, provides preliminary information on micronutrients and non-structural carbohydrates of selected aggregatum onion varieties of Tamil Nadu. Bangladesh J. Bot. 53(2): 243-247, 2024 (June)